2014
DOI: 10.5012/bkcs.2014.35.5.1545
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Superhydrophobic Surface on a Cellulose-based Material via Chemical Modification

Abstract: Superhydrophobicity is an interesting surface property underlying several fascinating natural phenomena, such as the self-cleaning ability of lotus leaves and the striding ability of spiders, which have attracted much interest in the industry and academia. A superhydrophobic surface is that on which the water contact angle (WCA) is higher than 150 o and the water sliding angle is lower than 10 o , hence, water droplets can easily slide/run off the surface. This principle of high water repellence of a superhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…Lee et al reported a superhydrophobic and superoleophilic cellulose fabric produced via a single step chemical reaction. [ 51 ] The strong coating was achieved through the esterifi cation reaction between hydroxyl groups on the cellulose surface and the stearic acid. The controllable in situ growth of inorganic nano-and microcrystals on textiles offers another way to achieve uniform coatings and tunable surface roughness.…”
Section: Textiles/fabricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al reported a superhydrophobic and superoleophilic cellulose fabric produced via a single step chemical reaction. [ 51 ] The strong coating was achieved through the esterifi cation reaction between hydroxyl groups on the cellulose surface and the stearic acid. The controllable in situ growth of inorganic nano-and microcrystals on textiles offers another way to achieve uniform coatings and tunable surface roughness.…”
Section: Textiles/fabricsmentioning
confidence: 99%
“…The functional groups (e.g., -OH) on many textile surfaces can be utilized for chemical reactions, i.e., covalently bonding with the coating reagents, to form a robust coating layer. [49][50][51] Inspired by the bio-adhesion of polydopamine, Wang et al prepared a polydopamine/SiO 2 coated cotton textile, which retained its superhydrophobicity after 90 cycles of oil/water separation experiments and long-time ultrasonic treatment, indicating a very robust adhesion of the coating. [ 50 ] It also showed excellent chemical durability in harsh conditions, such as strong acidic and alkaline solutions.…”
Section: Textiles/fabricsmentioning
confidence: 99%
“…To use commercial cotton as selective sorbent, it should be hydrophobically modified [43][44][45][46][47][48]. In very recent years, the fabrication of graphene/RGO-coated cotton has been investigated [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] Materials exhibiting superhydrophobic/superoleophilic properties have received significant attention for practical applications, such as oil/water separation. Various approaches, including synthesis of porous superhydrophobic/superoleophilic-conjugated polymers, 29 deposition of a CNT composite material on PU surface, 30 chemical vapor deposition, 31 electroless metal deposition with a self-assembled monolayer, 32 and chemical modification of cotton fabrics, 11 have been reported for the fabrication of superhydrophobic/superoleophilic surface.…”
mentioning
confidence: 99%
“…[1][2][3] The continued demand for techniques to clean up oil spills has triggered the development of highly effective and selective oil absorption materials. 4,5 Traditionally, activated carbon, 6,7 zeolites, 8,9 and fibers [10][11][12] have been used to remove and collect spilled oil. However, these materials have a number of drawbacks, such as nonselectivity, poor absorption, and difficult reusability.…”
mentioning
confidence: 99%